1987
DOI: 10.1111/j.1151-2916.1987.tb04892.x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Characterization of Poling Effects in PZT Ceramics

Abstract: Acoustic velocity and attenuation were measured in poled and unpoled lead zirconate titunate (PZT) ceramics prepared by sintering and hot-pressing under different conditions. Hot-pressed PZT was found to have attenuation vdues approximately I order of magnitude smaller than sintered PZT. For both materials, poling cliused a decrease in attenuation. Depolurization and phase transition phenomena were also observed at elevated temperatures using a novel laserultrasound technique in combination with conventional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…2(b) shows the susceptance curves above the Curie temperature. It can be seen that, compared with the acoustic method 14 in which the high-order echo is submerged by noise (Fig. 2 in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(b) shows the susceptance curves above the Curie temperature. It can be seen that, compared with the acoustic method 14 in which the high-order echo is submerged by noise (Fig. 2 in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Dong et al 9 measured the elastic moduli and internal frictions of barium titanate ceramics over a wide temperature range and found that a negative Poisson's ratio appeared around 60 ○ C. Using the DMA and dielectric analyzer, the phase transitions in PZT and barium strontium titanate ceramics were also investigated by Wang et al 10,11 It should be noted that the commonly used free-free beam method and the DMA method are primarily limited to the measurement on isotropic materials, i.e., they are not applicable to poled materials although some scholars had employed them on poled PZT ceramics. 12,13 The Young's modulus and internal friction of poled PZT ceramics had been measured by the acoustic method, 14 and it was found that the Young's modulus of poled PZT is larger than that of the unpoled one. Based on this, Friend et al 15 employed the measured longitudinal wave velocity to determine the poling state of piezoelectric ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the attenuation for the acoustic stack was varied as 0.25 dB/cm‐MHz (lower attenuation for the acoustic stack), 0.75 dB/cm‐MHz (original attenuation for the acoustic stack), and 2.25 dB/cm‐MHz (higher attenuation for the acoustic stack). These values are typical for materials used in ultrasound probes . To simplify our simulations, the entire acoustic stack was assumed to have the same attenuation even though the attenuation of the different layers of the probe would vary dramatically.…”
Section: Illustrative Simulationsmentioning
confidence: 99%
“…These values are typical for materials used in ultrasound probes. 16,17 To simplify our simulations, the entire acoustic stack was assumed to have the same attenuation even though the attenuation of the different layers of the probe would vary dramatically.…”
Section: Simulation Parametersmentioning
confidence: 99%
“…This aspect is important and draws considerable interest to the application of PZT-materials for structural health monitoring. Moreover, it should be noted that the particle layer exhibits a low damping factor and high signal transmission properties [30] . The stress detection technique based on the correlation between current emission and dipole moment generation inside bulk ferroelectric PZT-specimen is the subject of this work.…”
Section: Introductionmentioning
confidence: 99%